Relationship Marketing in Banking Sector – A Comparison Between Public and Private Banks - Kumar, Deepak; Arora, Priya (Gyan Management Journal, 2023)
Relationship marketing is the wide concept and important in modern times for better competition in the recent times. Berry (1983) introduced the term relationship marketing. Later on many research and debates conducted on the relationship marketing and the challenges and major issues faced by the service provider in order to maintain their customers. This paper attempt to summarize the Impact of relationship marketing on banking sector and comparison is made in order to understand about the status of relationship marketing in public and private banks.